RESTRICTED SELECTION INDEX FOR GROWTH TRAITS OF SHAMI KIDS - Khaleel I. Z. Jawasreh,; J. E. Al-Kass, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
A Restricted Selection Index was constructed to genetically evaluate animals using a dataset composed of body weights of Shami kids at the ages of birth, weaning, and 6-month. The variance-covariance matrix (VCV) was generated and used to estimate genetic parameters for the index construction after adjusting the fixed effects; year, birth month, kid sex, type (single, twin or triplet) of birth, doe age, weights at kidding (KW), birth (BWT) and weaning (WWT) as covariates. General Linear Model and Restricted Maximum Likelihood methods were used to estimate BLUE for fixed effects and variance components for random effects, respectively. BW was 3.6 ± 0.017, WW 16.8 ± 0.10, and weight at 6 months (MWT) was 26.7 ± 0.21 Kg. With the exception of buck origin and doe age, all tested factors significantly affected growth traits. Heritability for BWT, WWT, and MWT was 0.70 ± 0.10, 0.32 ± 0.075, and 0.41 ± 0.12, and repeatability was 0.78, 0.35, and 0.47, respectively. Genetic and phenotypic correlations were positive and significant between BWT and WWT, and between WWT and MWT. The restricted selection index constructed for increasing weights at MWT and WWT with restriction on BWT yielded a strong correlation coefficient (rIA) between the genetic merit and the index at 0.54 (p